An Unintended Consequence of IDEA: American Sign Language, the Deaf Community, and Deaf Culture into Mainstream Education - Rosen, Russell S. (Disability Studies Quarterly, 2006)
One goal of the Individuals with Disabilities Education Act (IDEA) is the integration of students who are deaf and hard of hearing into American society. Its original programmatic thrust, stated in the Education for All Handicapped Children Act (PL 94-142), is the fostering of speech and hearing skills and the placement of deaf and hard of hearing students in regular classrooms with hearing students. However, an analysis of historical and educational documents shows that IDEA unintentionally created the process for the inclusion of the language, community, and culture of signing deaf and hard of hearing students into the American education system. As IDEA integrates signing deaf and hard of hearing students into the American education system, American Sign Language (ASL) and the American Deaf community and culture are also mainstreamed into the system.